Determinan Kinerja Tenaga Perawat di Ruang Rawat Inap RSUD Bima Tahun 2023 - Amir, Amir; Sulaiman, Lalu; Menap, Menap (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Nursing services as an integral part of health services clearly have a significant contribution to the quality of services in hospitals, so that every effort to improve the quality of hospital services must also be accompanied by efforts to improve the quality of nursing services. The aim of this research is to determine the influence of education, motivation, incentives, and employment status on the performance of nurses in inpatient room of the Bima Hospital. This research method uses quantitative research with analytical observational. The research design used was a cross-sectional study. The research sample consisted of 134 people. Data were analyzed using bivariate analysis and the Chi Square test was carried out. The results of this research show that there is an influence of education, motivation, incentives on the performance of nurses in the inpatient room at Bima Regional Hospital with a p-value of 0.00 (p <0.05). Meanwhile, employment status has no influence on the performance of nurses in the inpatient room at Bima Hospital with a p-value of 0.507 (p > 0.05). Bima Hospital management is expected to always maintain employee performance by implementing governance based on education, motivation, and incentives.